Surface treatments for biological, chemical and physical applications - Gürsoy, Mehmet; Karaman, Mustafa (Wiley-VCH, 2017)
A step-by-step guide to the topic with a mix of theory and practice in the fields of biology, chemistry and physics. Straightforward and well-structured, the first chapter introduces fundamental aspects of surface treatments, after which examples from nature are given. Subsequent chapters discuss various methods to surface modification, including chemical and physical approaches, followed by the characterization of the functionalized surfaces. Applications discussed include the lotus effect, diffusion barriers, enzyme immobilization and catalysis. Finally, the book concludes with a look at future technology advances. Throughout the text, tutorials and case studies are used for training purposes to grant a deeper understanding of the topic, resulting in an essential reference for students as well as for experienced engineers in R&D.